Reduced preoperative serum choline esterase levels and fecal peritoneal contamination as potential predictors for the leakage of intestinal sutures after source control in secondary peritonitis - Amati, Anca-Laura; Ebert, R.; Maier, L.; Panah, Amir Kauveh; Schwandner, T.; Sander, M.; Reichert, M.; Grau, V.; Petzoldt, S.; Hecker, A. (World journal of emergency surgery, 2024)
Background: The high rate of stoma placement during emergency laparotomy for secondary peritonitis is a paradigm in need of change in the current fast-track surgical setting. Despite growing evidence for the feasibility of primary bowel reconstruction in a peritonitic environment, little data substantiate a surgeons’ choice between a stoma and an anastomosis. The aim of this retrospective analysis is to identify pre- and intraoperative parameters that predict the leakage risk for enteric sutures placed during source control surgery (SCS) for secondary peritonitis. Methods: Between January 2014 and December 2020, 497 patients underwent SCS for secondary peritonitis, of whom 187 received a primary reconstruction of the lower gastro-intestinal tract without a diverting stoma. In 47 (25.1%) patients postoperative leakage of the enteric sutures was directly confirmed during revision surgery or by computed tomography. Quantifiable predictors of intestinal suture outcome were detected by multivariate analysis. Results: Length of intensive care, in-hospital mortality and failure of release to the initial home environment were significantly higher in patients with enteric suture leakage following SCS compared to patients with intact anastomoses (p < 0.0001, p = 0.0026 and p =0.0009, respectively). Reduced serum choline esterase (sCHE) levels and a high extent of peritonitis were identified as independent risk factors for insufficiency of enteric sutures placed during emergency laparotomy. Conclusions: A preoperative sCHE < 4.5 kU/L and generalized fecal peritonitis associate with a significantly higher incidence of enteric suture insufficiency after primary reconstruction of the lower gastro-intestinal tract in a peritonitic abdomen. These parameters may guide surgeons when choosing the optimal surgical procedure in the emergency setting.